2020
DOI: 10.1186/s12967-020-02463-0
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the pattern of immune related cells and genes in the peripheral blood of ischemic stroke

Abstract: Background Ischemic stroke (IS) is the second leading cause of death worldwide which is a serious hazard to human health. Evidence suggests that the immune system plays a key role in the pathophysiology of IS. However, the precisely immune related mechanisms were still not been systematically understood. Methods In this study, we aim to identify the immune related modules and genes that might play vital role in the occurrence and development of IS by using the weighted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 54 publications
0
41
1
Order By: Relevance
“…As part of our ongoing BACTRAC study, our group has reported that using machine learning analysis, the gene expression of IL-7 is associated with infarct and edema volume ( Martha SR et al., 2020 ). Both IL7 and IL7R have been reported on in the context to ischemic stroke and prior studies have found plasma levels of both IL7 and IL7R were significantly lower in stroke cohorts as compared to controls ( Oberheiden et al., 2012 ; Li et al., 2020 ). Oncostatin M (OSM) is a cytokine belonging to the IL-6 family that is typically released by monocytes, macrophages, dendritic cells, and T lymphocytes under inflammatory conditions ( Hermanns, 2015 ).…”
Section: Discussionmentioning
confidence: 93%
“…As part of our ongoing BACTRAC study, our group has reported that using machine learning analysis, the gene expression of IL-7 is associated with infarct and edema volume ( Martha SR et al., 2020 ). Both IL7 and IL7R have been reported on in the context to ischemic stroke and prior studies have found plasma levels of both IL7 and IL7R were significantly lower in stroke cohorts as compared to controls ( Oberheiden et al., 2012 ; Li et al., 2020 ). Oncostatin M (OSM) is a cytokine belonging to the IL-6 family that is typically released by monocytes, macrophages, dendritic cells, and T lymphocytes under inflammatory conditions ( Hermanns, 2015 ).…”
Section: Discussionmentioning
confidence: 93%
“…The main advantage of this method is that it can cluster genes into co-expression modules, as well as build a bridge between gene expression changes and sample characteristics. Thus, WGCNA has been widely used in various malignant and non-malignant diseases ( Chen et al, 2020 ; Chen et al, 2019 ; Chen et al, 2018 ; Li et al, 2020a ; Zheng et al, 2020 ). In cancer research, more and more researchers have applied WGCNA for developing new prognostic biomarkers ( Xu et al, 2020 ; Chen et al, 2020 ; Chen et al, 2019 ; Chen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We imported the genes linked to the clinical progression into the STRING online web platform (https://string-db.org). Then, a PPI network was established with a minimum level of con dence> 0.9 [21]. The plug-in cytoHubba in Cytoscape v3.6.1 was employed to determine the top 10 genes in the network as the core genes via 3 algorithms: Betweenness, Maximal Clique Centrality, and Degree.…”
Section: Development Of Protein-protein Interaction (Ppi) Networkmentioning
confidence: 99%